The politics of trad e Egypt and lower Nubia in the 4th millennium BC - Roy, Jane. (Culture and History of the Ancient Near East, 2011)
Until recently much of the discussion regarding the A-Group has emphasised the influence of Egypt in the region. Egyptian material found in A-Group contexts has pointed to some type of exchange system between the two regions but the lack of A-Group manufactured objects in Egyptian contexts has led to the argument that the relationship was somewhat one-sided. Yet was it and how different were Egyptians and Lower Nubians during the 4th millennium BC? Re-examining the material evidence from three major archaeological salvage campaigns, and using anthropological and economic theories this book takes a fresh look at exchange patterns between Egypt and Lower Nubia. The changes and developments in these relationships potentially impacted the development towards the Egyptian state and the fate of the A-Group.